The emigrants - Moberg, Vilhelm, 1898-1973.; Lannestock, Gustaf (St. Paul : Minnesota Historical Society Press, 1995)
From the Publisher: Book One-introduces Karl Oskar and Kristina Nilsson, their 3 young children, and 11 others who make up a resolute party of Swedes fleeing the poverty, religious persecution, and social oppression of Smaland in 1850.
Introduction to the Emigrant novels -- Introduction to the Emigrants -- Bibliography for the Emigrant novels -- Suggested readings in English -- By way of introduction -- Peasants -- Country which they left -- Part 1: Gates On The Road To America -- 1: King in his stone kingdom -- 2: Farmhand who drowned in the mill brook -- 3: What the bedbugs in a stable room must listen to -- 4: Karl Oskar and Kristina -- 5: Ake returns from the insane asylum -- 6: Suitable chastisment -- 7: About a wheat field and a bowl of barley porridge -- 8: With God's help and through the assistance of the authorities -- 9: America chest -- 10: Peasant bows for the last time -- 11: One emigrant pays no fare -- 12: All gates open on the road to America -- Part 2: Peasants At Sea -- 13: Charlotta of Karlshamn -- 14: Forty paces long and eight paces wide -- 15: Cargo of dreams -- 16: Happenings on board the ship -- 17: Ship was covered with waves -- 18: Bushel of earth from Sweden -- 19: At home and away -- 20: Stories on the after deck -- 21: It was called ship-sickness -- 22: Story told at the main hatch -- 23: Peasants at sea -- 24: Long night -- 25: Another three shovelfuls of earth from Sweden -- 26: Sailing toward midsummer.
Includes bibliographical references (p. xxiii-xxv).
Keywords: Sweden -- Emigration and immigration -- Fiction